Brer Rabbit Down the Well - Retold by Stowell, Louie (London Usborne Publishing Ltd, 2009)
When Brer Fox tricks Brer Rabbit into falling down a well, he has to come up with a plan to get out mighty fast before the hunter comes
Include Color Illustration
Keywords: Brer Rabbit (Trickster) -- Rabbits -- Tales